Пространственно-временные вариации концентрации электронов в ионосфере в минимуме и максимуме солнечной активности - Ляшенко, Михаил Владимирович; Шницар, Игорь Романович (НТУ "ХПІ", 2017)
Представлены результаты экспериментальных исследований вариаций концентрации электронов в ионосфере по данным харьковского радара некогерентного рассеяния, полученных на фазах минимума (2006 – 2007 гг.) и максимума (2012 – 2013 гг.) цикла солнечной активности. Выполнен анализ и физическая интерпретация пространственно-временных зависимостей концентрации электронов. Представлены результаты моделирования суточных вариаций концентрации электронов в диапазоне высот 190 – 790 км в рамках развития региональной модели ионосферы CERIM IION.

Results of experimental investigations of variation of electron concentration in ionosphere on Kharkiv incoherent scatter radar data obtained during the phases of the minimum (2006 – 2007) and the maximum (2012 – 2013) of the solar activity cycle are presented. Analysis and physical interpretation of spatial-temporal dependencies of the electron concentration variations were carried out. Modeling results of the diurnal variations of the electron concentration in the altitude range 190 – 790 km in the frame of CERIM IION regional model of ionosphere development are presented.
The spatial-temporal variations of the electron concentration in ionosphere in minimum and maximum of solar activity
Keywords: концентрация электронов; региональная модель ионосферы; фазы цикла солнечной активности; electron concentration; regional model of ionosphere; phases of solar activity cycle